Making sense of change management : a complete guide to the models, tools and techniques of organizational change - Cameron, Esther. (Kogan Page, 2015)
"Making Sense of Change Management is the best-selling classic text, providing a thorough overview of the subject of change for both students and professionals. Along with explaining the theory and practice of change management and comprehensively covering the models, tools, and techniques of successful change management, this completely revised and updated fourth edition includes more international examples and case studies throughout the book. The chapter on cultural change has been re-written to reflect the emerging new thinking and practice in this area, offering ways to help managers implement cultural change processes within their organization. It also explores cultural sensitivity and what to do when cultures collide.Additionally, the chapter on IT based process change has now been replaced with one on the inter-relationship with project management (PM) and change management. It defines "project success," explains how PM approaches are increasingly being used to manage transformational change, and covers complexity models, agile approaches, and stakeholder management.With free online resources for professors/instructors, this is an ideal textbook for MBA or graduate students focusing on leading or managing change"--